Influence of quenching and annealing heat treatments on the strain hardening properties of AISI steels: a statistical approach - Ricardo Andrés García-León; Haidee Yulady Jaramillo; July Gomez-Camperos (Dyna)
The knowledge of the stress-strain curve is of great interest due to the different parameters, conditions, and applications to which materials are exposed in different industrial sectors. This statistical study aims to analyze the strain-hardening behavior of two AISI-grade materials (1045 and 304). The ASTM E-8 standard procedure guidelines were considered for different hardening percentages due to plastic deformation (20% and 40%), following an experimental design of 45 tests, including repetitions. The results revealed an improvement in the material's mechanical properties corresponding to the hardening percentage, which was also correlated with the heat treatment process. Finally, response surface methodology plots were generated, depicting predictive equations governing the behavior of the response variables (stress, yield, load, and strain) with a confidence level of 98% in the results.